Fatigue Influence Factors and Coping Strategies among Cancer Patients’ Spouses: A Quantitative Study in China - Yao, MS, Dazhi; Guo, MS, Yanping; Yuan, BS, Shuai; Zhang, MS, Quanzhi (North American Journal of Medicine and Science, 2017)
The objective of this study aimed to: 1) identify how demographic variables, coping style, and psychological symptoms affect fatigue in Cancer Patients’ Spouses, and 2) explore the relationship between fatigue and coping style in cancer patients’ spouses. The methods used in this study include cross-sectional study design. 314 cancer patients’ spouses were recruited from the northeast part of China. Participants completed a socio-demographic form, Symptom Checklist-90, Trait Coping Style Questionnaire, and Fatigue Scale-14. Multiple linear stepwise regression analyses were used to test fatigue affect factors. Summarily, the demographics information show that the majority of the participants were middle age, most of whom (64%) age range 41-60. Cancer type include lung (30.3%), colorectal (13.7%), stomach (12.4%), breast (27.4%), etc. Significant predictors for fatigue are financial burden (β = -0.30, P < 0.001), current poor health (β = -0.22, P < 0.001), care-giving time (β = 0.12, P = 0.031), age (β = 0.12, P = 0.042), obsessive-compulsive (β = 0.34, P = 0.014), somatization (β = 0.37, P = 0.004), hostility (β = -0.25, P = 0.005), negative coping (β = 0.25, P < 0.001), positive coping (β = -0.14, P = 0.005), and positive coping is the predictor for lower fatigue (β = 0.20, P = 0.008). The conclusion of this study is that the fatigue experienced by cancer patients’ spouses is related to factors such as demographic variables, coping style, and psychological health; positive coping may be a mediator between mental fatigue and psychological symptoms. [N A J Med Sci. 2017;10(2):45-52. DOI: 10.7156/najms.2017.1002045]